ANOHOVY FISHERY OF SOUTHWEST COAST OF INDIA WITH NOTES ON CHARACTERISTICS OF THE RESOURCES - Luther, G (Indian Journal of Fisheries, 2011)
A study of the monthly anchovy fishery data from the eleven fishery survey zones along the southwest coast of India lying between Cape Comorin and the northern border of Kerala coast has revealed that the southern region lying between Cape Comorin and Quilon is most productive for the anchovies, landing annually a little over 10,000 tonnes. This forms about 70% of the anchovy catch landed along the southwest coast. Stolephorus devisi ond S. bataviensis are the commercially important anchovies along the southern region. There are two fishery seasons in the southern region, one during January-May and other during September- November; but only a single season extending from July to November is present in the northern region. The main fishery season throughout the southwest coast, however, is during September-November. The possibility of increasing the anchovy catch between Quilon and Ratnagiri has been pointed out. The present state of utilization of the catch and marketing are outlined, together with some suggestions for their improvement. Some details of thÂ« fisheries and biological characteristics of the anchovies of the Vizhinjam area are given. As the anchovy fishery is mainly supported by fishes of the ’O’ year class, anchoviss are to be regarded as an aTinually renewable fishery resource. There is multiple spawning of individual fish and the spawning season of each species is also prolonged. The ’Nonnavu’ fishery which takes a great toll of the young juvenile of Stolephorus spp., and its impact on the larger-sized anchovy fishery resources deserve detailed investigation